Contamination Alert: Microbial and Heavy Metal Levels in Green Vegetables: Peringatan Kontaminasi: Tingkat Mikroba dan Logam Berat pada Sayuran Hijau - Ali, Naqaa K. (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigated microbial and heavy metal contamination in leeks, a staple green vegetable, focusing on seasonal variations and contamination sources. One hundred leek samples were analyzed for Escherichia coli, Klebsiella, and heavy metals such as zinc, copper, and lead. Findings indicated contamination was higher in district areas compared to city centers, with the highest concentrations of zinc reaching 28.41 ppm during the summer. Results highlight the urgent need for improved contamination prevention measures and increased health awareness to ensure vegetable safety. Highlights: Higher District Contamination: Microbial levels were notably higher in district areas compared to city centers. Seasonal Metal Peaks: Zinc concentration spiked during the summer, reflecting seasonal impacts on heavy metal levels. Urgent Safety Measures: The results call for urgent improvements in contamination prevention and public health education. Keywords: Vegetable Safety, Microbial Contamination, Heavy Metals, Seasonal Variation, Public Health Awareness